Sustaining abundance : - Scruggs, Lyle (Cambridge University Press, 2003)
Representing the first comprehensive study of its kind, this book evaluates the comparative performance of national environmental policies since the beginning of the modern environmental era. Unlike other comparative studies, it looks directly at the purpose of environmental policy: pollution reduction.